An Ultrawideband Bidirectional Absorptive Common-Mode Filter With All-Pass Signal Transmission - Yu-Hsiang Chen; Cheng-Nan Chiu (IEEE Access, 2022)
This study proposes a miniaturized strip-line absorptive common-mode filter using a novel and ingenious defected ground structure (DGS). The proposed filter is bidirectional and has an ultrawide absorption band to stop the common-mode noise. The fractional bandwidth was as large as 147%. In addition, the filter allows the total transmission of differential signals of up to approximately 15 GHz, as determined by the 3-dB cutoff frequency. Both noise absorption and signal transmission bandwidths have never been reported in the literature. An equivalent circuit model and design principle were proposed. Accordingly, a filter prototype with a total area of 1.1% of the square of the wavelength at the lowest frequency of the absorption band is designed and implemented. The measured results verified the design and demonstrated its claimed performance.